The development of career pathway framework for early childhood care and education: Malaysia context - Saari, Erni Marlina; Mohamad Rasli, Roznim; Abdul Aziz, Nor Azah (Southeast Asia Early Childhood Journal, 2021)
The educational sector plays an important role in delivering quality education in order to build better nations by striving for excellence. Career development is filled with many challenges encompassing financial, economic, logistical and social factors. The challenges are mainly on quality, qualification, language and ethnicity. Specifically, unclear career pathway, limited information, internet access and job positions, training, special needs training, policies, promotion, no funding, no standardized wage charter guidelines, pursue study and lack of support. This study focuses on the framework of the orientations and challenges related to career pathway faced by in-service educators namely edu-carer and assistant. Methodology used in this study are document analysis and thematic analysis of interview data from public and private Early Childhood Care and Education in Malaysia. The results show there are five important elements that contribute to the development of career path among the ECCE educators. These include the appropriate plan of career pathway for each individual, assessment carried out by the superiors to identify individual’s performance and its implication to the children development, sufficient and appropriate trainings either skills or knowledge, requirement of incentives and reward for self-improvement and the support, encouragement and facilitation from the superiors. This study impact on individual growth and development not only professionally but also personally, by plotting a course for identifying occupational interests, determining education and training needs and verifying an action plan for reaching career goals.  In sum, the standardize framework for EECE career pathway had been developed that is beneficial to all parties.